2009
DOI: 10.1002/mame.200900181
|View full text |Cite
|
Sign up to set email alerts
|

Benzoylgermanium Derivatives as Novel Visible‐Light Photoinitiators for Dental Composites

Abstract: New dibenzoylgermanium derivatives are synthesized starting from various dithioacetal protected benzaldehydes by a coupling reaction with different dialkyldichlorogermanes and subsequent oxidative cleavage of the protecting group. The synthesized germanium compounds show a significantly stronger blue light absorption than camphorquinone. During irradiation, the dibenzoylgermanium derivatives undergo photodecomposition under formation of radicals. Therefore, the different dibenzoylgermanium derivatives are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 17 publications
0
87
0
2
Order By: Relevance
“…Another example of modification of the initiator technology is Tetric EvoCeram Bulk Fill (Ivoclar-Vivadent). This material utilizes a germanium-based photoinitiator, with maximum wavelength of absorption at 420 nm [89]. This molecule presents a much higher quantum yield than the camphorquinone/amine system, and also results in the formation of two active radicals, which may facilitate propagation of reactive species even at depths where the light intensity is significantly diminished [89].…”
Section: Bulk-fill Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of modification of the initiator technology is Tetric EvoCeram Bulk Fill (Ivoclar-Vivadent). This material utilizes a germanium-based photoinitiator, with maximum wavelength of absorption at 420 nm [89]. This molecule presents a much higher quantum yield than the camphorquinone/amine system, and also results in the formation of two active radicals, which may facilitate propagation of reactive species even at depths where the light intensity is significantly diminished [89].…”
Section: Bulk-fill Materialsmentioning
confidence: 99%
“…This material utilizes a germanium-based photoinitiator, with maximum wavelength of absorption at 420 nm [89]. This molecule presents a much higher quantum yield than the camphorquinone/amine system, and also results in the formation of two active radicals, which may facilitate propagation of reactive species even at depths where the light intensity is significantly diminished [89]. In vitro investigations have demonstrated that these materials may require at least 20 s of photoactivation to achieve levels of conversion comparable to incrementally placed conventional composites [90].…”
Section: Bulk-fill Materialsmentioning
confidence: 99%
“…The glass fillers were silanized analogous to the method already reported in literature [18]. Typically, the glass fillers were silanized by mixing them with 1 wt% of water and 5 wt% of 3-glycidyloxypropyltrimethoxysilane at room temperature over a period of 2 h, and drying the modified fillers at 50 °C for 4 days.…”
Section: Resultsmentioning
confidence: 99%
“…Ivocerin® (0.2 mol%) was added as photoinitiator. [32] Homopolymerization of phosphonates 3a, 3b, 8a, Scheme 2. synthesis of monomers 9a and 9b. Scheme 3. synthesis of monomer 10.…”
Section: Photopolymerization In Bulkmentioning
confidence: 99%